Implementasi Sistem Manajemen Keselamatan dan Kesehatan Kerja di PT X - Devira Rona Prisnayanti; Evi Widowati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Industry is a form of all economic activities in the form of processing raw materials and utilizing resources that aim to produce goods that have benefits and more value. In Indonesia, the manufacturing industry sector experienced a rapid increase of 5.1%. Correspondingly, in 2017 around 13.7% or 380,000 deaths were caused by work accidents, while 86% or around 2.4 million deaths were due to occupational diseases. Based on the company's accident data, at PT Surya Mandiri Jaya Sakti, it increased in 2020 by 11%. In 2021, work accident cases increased to 12 cases. Meanwhile, the latest data from July 2022 to June 2023 has recorded 10 cases of work accidents. The implementation of the Occupational Safety and Health Management System (SMK3), is one of the important efforts in reducing the number of work accidents based on Government Regulation Number 50 of 2012. The type and design of this research is descriptive qualitative. The data collection technique uses observation by conducting semi-structured interviews, where the results will be tested for data validity using data triangulation techniques. The results showed that the implementation of the Occupational Safety and Health Management System (SMK3) at PT Surya Mandiri Jaya Sakti based on Government Regulation Number 50 of 2012 at the initial level as many as 40 indicators out of a total of 64 indicators have been fulfilled, so that the percentage is 63% and those that have not been fulfilled are as follows.